Development of Research-Based Learning Model in Biology Education: What is Relevance, Concystency and Practicality? - M. Haviz (Journal of Education and Learning (EduLearn), 2018)
The purpose of this article is to design a consistent research-based learning model and internal relevance on biology learning at Higher Education. The study participants were 88 students of Biology Education Department IAIN Batusangkar who studied Research Method subjects in Biology study, academic year 2016/2017. The method used was educational design research with preliminary stages of research, prototyping stage, and assessment stage. The instruments used were product assessment sheets. Preliminary research findings were analysed by reducing, presenting, and drawing conclusions. The mean score of formative evaluation result and mean score of the students’ achievement were analysed by descriptive statistic. Preliminary research results showed that changes should be made toward the biology learning outcomes. The next finding was that there were 9 supporting theories used to design research-based learning models on biology learning. Formative and summative prototype evaluation results were good and had met the criteria of developing the learning model. So, it was concluded that research-based learning model on biology learning had consistency and internal relevance.